Sustainable Energy - Technological Issues, Applications and Case Studies 2016
DOI: 10.5772/65015
|View full text |Cite
|
Sign up to set email alerts
|

Clean Water from Clean Energy: Decentralised Drinking Water Production Using Wind Energy Powered Electrodialysis

Abstract: Supply of potable water requires energy and unfortunately most of the countries with minimal access to safe drinking water are also poor in terms of access to reliable energy grids. However, many of such regions have access to other sources of water (such as brackish and groundwater) that can be treated for producing drinking water if correct treatment systems are put in place. Moreover, many of the electrically remote areas are rich in terms of renewable energy (RE) resources (such as wind and solar) which ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 97 publications
(140 reference statements)
0
1
0
1
Order By: Relevance
“…Cirez et al [22] developed a flexible PV-ED system using an optimized PV module design, which was composed of multiple connected PV cells in series/parallel that could vary voltage applied to the ED stack and maximize energy transfer given available solar irradiance. Malek et al [23] demonstrated robust and stable desalination performance in a lab-scale, directly-coupled, wind-powered ED system under various wind speeds, turbulence intensities, and periods of oscillation. The study indicated that specific energy consumption of the process was relatively unaffected by fluctuations tested in the lab-scale wind-ED system [21].…”
Section: Review Of Prior Workmentioning
confidence: 99%
“…Cirez et al [22] developed a flexible PV-ED system using an optimized PV module design, which was composed of multiple connected PV cells in series/parallel that could vary voltage applied to the ED stack and maximize energy transfer given available solar irradiance. Malek et al [23] demonstrated robust and stable desalination performance in a lab-scale, directly-coupled, wind-powered ED system under various wind speeds, turbulence intensities, and periods of oscillation. The study indicated that specific energy consumption of the process was relatively unaffected by fluctuations tested in the lab-scale wind-ED system [21].…”
Section: Review Of Prior Workmentioning
confidence: 99%
“…Im Unterschied dazu bietet die Nutzung erneuerbarer Energiequellen die Möglichkeit einer nachhaltigen und emissionsarmen Wasserentsalzung [10][11][12]. Durch den Einsatz derartiger dezentraler Wasserentsalzungsanlagen auf Basis erneuerbarer Energien können zusätzlich neben dem Vorteil der Netzunabhängigkeit Kosten für den Wassertransport entfallen [13,14].…”
unclassified